Therapeutic targeting cancer-initiating cell markers by exosome miRNA: efficacy and functional consequences exemplified for claudin7 and EpCAM1 - Kyuno, Daisuke; Zhao, Kun; Bauer, Nathalie; Ryschich, Eduard; Zöller, Margot (Translational oncology, 2019)
AIM: Transfer of exosomes (Exo) miRNA was described interfering with tumor progression. We here explored for claudin7 (cld7) and EpCAM (EpC), cancer-initiating-cell markers in colorectal and pancreatic cancer, the efficacy of Exo loading with miRNA and miRNA transfer. METHODS: Exo were collected from nontransformed mouse (NIH3T3) and rat lung fibroblasts (rFb), which were transfected with Tspan8 cDNA (NIH3T3-Tspan8, rFb-Tspan8). Exo were loaded by electroporation with miRNA. The transfer of Exo-miRNA was evaluated in vitro and in vivo in a rat pancreatic (ASML) and a human colon (SW948) cancer line. RESULTS: NIH3T3-Tspan8- or rFb-Tspan8-Exo were efficiently loaded with cld7- or EpC-miRNA. Exo targeting in vivo was strongly improved by tailoring with Tspan8. Exo-miRNA transfer into tumor targets promoted cld7, respectively, EpC downregulation by 33%-60%. Cld7 silencing was accompanied by reduced expression of additional cancer-initiating cell markers and NOTCH. EpC silencing reduced vimentin, N-cadherin, and Nanog expression. The Exo-miRNA transfer affected anchorage-independent growth, motility, and invasion. CONCLUSIONS: Exo are efficiently loaded with miRNA, miRNA-delivery being supported by Exo tailoring. Partial cld7 and EpC silencing by Exo miRNA affects metastasis-promoting tumor cell activities. The findings suggest miRNA loading of tailored Exo as an easy approachable and efficient adjuvant therapy.
Available online 28 October 2018
Im Titel ist "1" in EpCAM1 hochgestellt
Gesehen am 04.04.2019